Framework Teknologi Multimedia untuk Pengajaran Bahasa Inggris - Mita Nur Aflah; Gina Selvira Yanti (IKIP PGRI Bojonegoro, 2019)
AbstractTechnology plays an important role in teaching and learning process. The use of technology in the classroom helps practitioners to improve the effectiveness of learning. Concerning with these facts, it is necessary to have specific guidelines regarding the implementation of technology in the classroom to optimize the benefits of the technology. This study aims to explain the notion of technology integration and its use in the classroom. It provides multimedia technology-based teaching framework contains activities that can be used by teachers or lecturers to be applied in the classroom. This study also explains some of the literature from previous researchs on the use of multimedia technology which has the role of improving students English language skills. Hopefully, this research can be useful for educators to integrate multimedia technology in the classroom.Â Keywords: multimedia technology, technology integration, language teaching.Â AbstrakTeknologi telah memainkan peran penting dalam proses belajar mengajar. Pemanfaatan teknologi di dalam maupun di luar kelas telah membantu para praktisi pendidikan untuk meningkatkan efektivitas pembelajaran. Berangkat dari fakta tersebut maka perlu adanya panduan khusus mengenai penerapan teknologi di dalam kelas guna mengoptimalkan manfaat dari teknologi tersebut. Penelitian ini bertujuan memaparkan pengertian integrasi teknologi beserta pemanfaatannya di dalam kelas. Dilengkapi pula dengan framework pengajaran berbasis teknologi multimedia yang berisikan aktivitas yang dapat digunakan para guru atau dosen untuk diterapkan di dalam kelas. Penelitian ini juga menjelaskan tentang beberapa literatur dari penelititan sebelumnya mengenai penggunaan teknologi multimedia yang telah berperan meningkatkan keterampilan Bahasa Inggris peserta didik. Harapannya, penelitian ini dapat menjadi referensi untuk para pendidik dalam mengintegrasikan teknologi multimedia di dalam kelas. Â Kata kunci: teknologi multimedia, integrasi teknologi, pengajaran bahasa.